Takeda G protein–coupled receptor 5 (TGR5): an attractive therapeutic target for aging-related cardiovascular diseases - He, Yufeng; Liu, Siqi; Zhang, Yali; Zuo, Yumei; Huang, Keming; Deng, Li; Liao, Bin; Zhong, Yi; Feng, Jian (Frontiers in Pharmacology, 2025)
Aging is an independent risk factor for many chronic diseases, including cancer and cardiovascular, pulmonary, and neurodegenerative diseases. In recent years, the mechanisms of aging-related cardiovascular diseases (CVDs) have been studied intensively. Takeda G protein-coupled receptor 5 (TGR5) is a membrane receptor for bile acids that has been found to play an important role in various disease processes, such as inflammation, oxidative stress, and metabolic disorders, all of which contribute to aging-related CVDs. In this review, we summarise the role of TGR5 in aging-related CVDs and propose TGR5 as an attractive therapeutic target based on its mechanism of involvement, which may contribute to future drug target design.